2022
DOI: 10.1029/2022gl099809
|View full text |Cite
|
Sign up to set email alerts
|

Resolving the Tectonic Setting of South China in the Late Paleozoic

Abstract: The late Paleozoic was a dynamic and crucial time in the evolution of the Earth system. It is characterized by the assembly of supercontinent Pangea (Metcalfe, 2013;Stampfli et al., 2013), superplume activities embodied by the Skagerrak-Centered large igneous province (LIP),

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 80 publications
0
7
0
Order By: Relevance
“…Distribution map of igneous rocks in Hainan Island (The blue frame shows the igneous rocks in the post‐collision extensional tectonic setting, data from Chen, 2020; Chen et al, 2011; Chen, Wang, et al, 2013; Chen, Lin, et al, 2013; Dilek & Tang, 2020; Ding et al, 2005; Du, 2022; Gao, Chen, et al, 2022; Gao, Shi, et al, 2022; Gou et al, 2019; He et al, 2016; He, Wang, Xin, & Zhang, 2018; Hu et al, 2022; Li et al, 2013; Liu, 2016; Liu, Hu, et al, 2022; Long et al, 2022; Tang, 2010; Wen et al, 2013; Xie et al, 2005; Yuan et al, 2019; Zhao et al, 2020). …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Distribution map of igneous rocks in Hainan Island (The blue frame shows the igneous rocks in the post‐collision extensional tectonic setting, data from Chen, 2020; Chen et al, 2011; Chen, Wang, et al, 2013; Chen, Lin, et al, 2013; Dilek & Tang, 2020; Ding et al, 2005; Du, 2022; Gao, Chen, et al, 2022; Gao, Shi, et al, 2022; Gou et al, 2019; He et al, 2016; He, Wang, Xin, & Zhang, 2018; Hu et al, 2022; Li et al, 2013; Liu, 2016; Liu, Hu, et al, 2022; Long et al, 2022; Tang, 2010; Wen et al, 2013; Xie et al, 2005; Yuan et al, 2019; Zhao et al, 2020). …”
Section: Discussionmentioning
confidence: 99%
“…For example, the 248 ± 1 Ma diorite porphyrite vein in the Shilu area (Li et al, 2013) and the 247.4-252 Ma shoshonitic intrusive rocks in Bawangling (Liu, 2016) were formed in the post-orogenic extensional setting. The detrital zircons from this period have F I G U R E 1 1 Distribution map of igneous rocks in Hainan Island (The blue frame shows the igneous rocks in the post-collision extensional tectonic setting, data from Chen, 2020; Chen et al, 2011;Chen, Lin, et al, 2013;Dilek & Tang, 2020;Ding et al, 2005;Du, 2022;Gao, Chen, et al, 2022;Gao, Shi, et al, 2022;Gou et al, 2019;He et al, 2016;He, Wang, Xin, & Zhang, 2018;Hu et al, 2022;Li et al, 2013;Liu, 2016;Liu, Hu, et al, 2022;Long et al, 2022;Tang, 2010;Wen et al, 2013;Xie et al, 2005;Yuan et al, 2019;.…”
Section: Provenance Of Detrital Zircons In Qionghaimentioning
confidence: 99%
See 1 more Smart Citation
“…For the North China Craton, westward subduction of the Paleo‐Pacific plate is inferred to have commenced at least in the Early Jurassic (Wu et al., 2019; Zhu & Xu, 2019). For South China, the earliest record of subduction of the Paleo‐Pacific plate can be traced back to 500 Ma (Gao et al., 2022; Isozaki et al., 2010; Pastor‐Galán et al., 2021), whereas Li and Li (2007) proposed that subduction started in the Permian. In contrast, other researchers suggested that subduction did not commence until the Triassic (Zhu et al., 2013), Early Jurassic (Xu et al., 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Much attention has been paid to fluorite in recent years, and countries and organizations such as China, the United States, Australia, and the European Union, classify it as a strategic and critical mineral [4][5][6]. South China is tectonically formed by the amalgamation of the Yangtze Block and Cathaysia Block [7,8] (Figure 1a) and is rich in fluorite resources, accounting for more than 80% of the total known fluorite reserve in China [9]. Fluorite deposits in South China can be classified into three major types: (1) hydrothermal fluid filling type;…”
Section: Introductionmentioning
confidence: 99%